Science and Spiritualism in an Irish Context: The Psychical Research Networks of William Fletcher Barrett - McCorristine, Shane (Aries, 2022)
William Fletcher Barrett (1844–1925) has long been recognised for his key role in the foundation of the Society for Psychical Research in 1882, but this came after years of working as a physicist and psychical researcher between Ireland and Britain, conducting mesmeric experiments, maintaining correspondence, and sharing research ideas at forums like the British Association for the Advancement of Science. This article re-evaluates Barrett’s career by focusing on his networks, projects, and organisations in Ireland. These acted as bridges connecting his work as a teacher of physics with his work as a psychical researcher and investigator of spiritualism. In doing so, this article also contributes to the history of spiritualism in Ireland by demonstrating the rich connections which existed between scientists, intellectuals, and amateur investigators in the area of spiritualism and psychical research.